IDENTIFY THE USE OF FUTURE TENSE IN RICK AND MORTY SHOW BY JUSTIN ROILAND & DAN HARMON - Sulthan Gibran Junaedy (Faculty of Education and Teachers Training, 2021)
Learning about grammar is essential for EFL students. To different people, the Word Grammar means different things. To the average person, it refers to the correctness or incorrectness of the words they use. It entails a logical and terminological analysis of sentences for a school student. Grammar knowledge helps the student in the correction of errors and the progress of written work. Only through unconscious assimilation can a person learn a foreign language accurately. Learning grammar is essential because it is indispensable for the student. Grammar is the system of a language. Grammar is often referred to as a language's